Improve students' ability to understand English learning material through a personal approach to students. - Iis Nurul Hasanah; Ahmad Sulthan Adil Lillah; Muhammad Zayyan Faiz An-nur; Siti Maemunah; Farida Hamid (Institut Agama Islam Negeri Palopo, 2024)
Personal and genre-based approaches are an approach to learning English as an EFL language, specifically in narrative text writing. So far, no research has conducted a comprehensive comparative analysis between these two approaches. The purpose of this study is to determine which of the personal approach and genre-based approaches is more suitable for practical application in teaching narrative writing in EFL classrooms. By using the qualitative design through post-tests in writing narratives, and then interviews. The participants were 11th graders at SMK YMJ CIPUTAT. The results show that the genre-based approach in writing narrative text is more effective and interesting and students prefer the genre-based approach, based on the analysis of student writing with a total score of 82, while the personal approach (experience) with a score of 76, but personal experience can provide an alternative writing method that is interesting to students. Therefore, the genre-based approach can be used as the main method in learning to write, while the personal approach can be used as a complementary method.